ASSOCIATION OF SHORT-TERM BLOOD PRESSURE VARIABILITY WITH DIABETES IN HYPERTENSIVE INDIVIDUALS. (June 2022) - Sousa, Andréa Cristina; Magalhães, Fabrício Galdino; Silva, Suelen Benta; Simeoni, Adélia Rocha; Inuzuka, Sayuri; Batista, Sandro Rogério; Vale, Raquel Mendonça; De Souza, Weimar Kunz Barroso; Sousa, Ana Luiza Lima
Abstract : Objective: Evaluation of short-term blood pressure (BP) variability and its associations with blood pressure measurements, in the different periods nalysed by Ambulatory Blood Pressure Monitoring (ABPM), in hypertensive patients with or without diabetes. Design and method: Analytical cross-sectional study, developed with a database containing 25-year historical series (1993 - 2018) of ABPM exams; diabetes is considered as comorbidity for hypertension. Variables nalysed: Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP) of 24 h, daytime and nighttime; Standard deviation; coefficient of variation SBP and DBP, nocturnal drop, age and body mass index. Accomplished logistic regression analysis, Confidence Interval of 95% and 5% of significance level. Results: Analyzed 1591 exams, identified 281 (17.7%) as diabetic hypertensives. Diabetics were older, (63.0; ± 10.9) than non-diabetics 57.7 (±13.9) and also had higher body mass index (28.9; ± 5.0 - 26.7; ± 4.4); with similar gender distribution. A higher proportion of uncontrolled nocturnal BP was identified among diabetics with 77.5% and 68.1% among non-diabetics. In the multivariate logistic regression analysis, considering in the model the presence or absence of DM as the dependent variable, the associated predictor variables were age (OR 1.04; 95% CI 1.01 - 1.08); media DBP in wakefulness (OR 1.34; IC95% 1.04 - 1.85), IMC (obese/non obese) (OR 2.35; 95%CI 1.18 - 4.66). The Coefficients of variation of blood pressure, systolic or diastolic, showed no significant association with the presence of DM morbidity along with HA. Analysis of the medium Coefficient of Variation of Systolic Blood Pressure showed decreasing measures in 24 hours, daytime, nighttime, similarly between diabetics and non-diabetics. A total of 229 (83.3%) no dipper diabetics and 973 (74.5%) of non-diabetics were identified. (p = 0, 002). Diabetics had significantly lower control rate than non-diabetics in the 24-hour period and during nigttime. Conclusions: It was identified that diabetic hypertensives were older, had lower blood pressure control during the nighttime period, with a lower proportion of non-dippers and were more obese. The pressure variation coefficients showed the same pattern between diabetics and non-diabetics.